Complexity and Public Policy: Network Model of Food Security Policy Implementation in Bone Regency - Novayanti Sopia Rukmana S; Alwi Alwi; Gita Susanti (Indonesian Association for Public Administration (IAPA), 2019)
Complexity and public policy are two things that cannot be separated. Determination and implementation of public policies is a complex process of interaction of all stakeholders loaded with interests, power, information, skills, and other resources. This shows the complexity in public policy that is not possible to be handled by the government alone but needs to involve all other stakeholders. So that to improve policy performance it is necessary to develop a network of all stakeholders in the implementation of public policy. This study aims to develop a network model in implementing food security policy in Bone Regency. This research was carried out in Bone Regency using a qualitative approach. Data sources used are primary data and secondary data. Data collection is done through interviews and observations. The results of this study indicate that the implementation of food security policy has not been effective. This is due to the lack of integrated food programs by all stakeholders. In this case, government agencies each design a food security program individually. Then, the Food Security Council as a network-based organization has not carried out its function in coordinating and synergizing stakeholders to design food programs that can prosper the people. As a result, poverty and food insecurity are still high in Bone Regency.